Tomographical evaluation of subsurface mineral composition in Ozalla, Edo State Nigeria - O.R. Ehidiamen; J.I. Ehilenboadiaye; C.I. Omoigiade (Journal of Applied Sciences and Environmental Management, 2019)
The subsurface is made up of distinct geologic materials existing at various depths. In a basement complex terrain, the lithologic unit that can be noticed is made up of the weathered layer, weathered/fracture basement and fresh basement. This research work was carried out at Ozalla community in Owan West Local Government Area of Edo State Nigeria, The study area is a basement complex area with some parts as transition zone, two dimensional geoelectrical resistivity survey was use to determine the subsurface resistivity distribution of the subsurface and interpreted with Res2Divn software to determine the subsurface Lithology and the mineral composition of the study area. The result from the study shows some buried subsurface minerals from the tomography images of the subsurface shows that at a depth between 10 m to 12 m reveals the composition of Alluvium soil, Shale, Slate, Sandstone, while at a depth between 13 m to the last depth of investigation reveals Quartz, Marble, Basalt, and Granite with apparent resistivity values ranging from 50 Ωm to 1500 Ωm. From the obtained results, slightly weathered/schist formation are the aquifer zone which shows that borehole drilling in this area is achievable at the depth of 40m, which allow big reservoir within the aquifer unit and overburden is thick enough for aquifer to accommodate high ground water potential due to presences of permeable rock.